New light on the Neolithic Fertile Coast: Recent excavations on Ghagha Island (Abu Dhabi Emirate, UAE) and the emergence of domestic architecture in ancient Arabia - Hameli, Noura; Cuttler, Richard; Beech, Mark; Crassard, Remy; al-Hajj al-Faki, Ahmed; Magee, Peter; Lidour, Kevin (Proceedings of the Seminar for Arabian Studies, 2023)
Ghagha island is located at the westernmost extent of Abu Dhabi emirate, approximately 1km from the UAE mainland. Survey and excavation by the Department of Culture and Tourism: Abu Dhabi, has identified two previously unknown Neolithic sites on the island (GHG0014 and GHG0063). GHG0014 comprises a cluster of stone-built rooms, preserved to nearly one metre in height. GHG0063 is still under excavation but comprises ash lenses and stone features. Finds from both sites include bifacial barbed and tanged arrowheads, plaster vessels fragments and other stone implements. Radiocarbon dates from GHG0014 indicates that it was occupied by 6500 cal BC. This is considerably earlier than any known domestic architecture in the region. A single assay from GHG0063 is in broad agreement with this chronology. In this paper we explore the implications of these discoveries for Neolithic coastal life in the Arabian Gulf, especially considering our growing understanding of the Flandrian Transgression. In addition, we position these discoveries against the normative framework which sees trade with Ubaid period Mesopotamia as a catalyst for economic change. Lastly, we explore how both sites, in combination with the discoveries from Marawah island, can disarticulate the linear narrative of the Neolithic Revolution in the ancient Near East.